Advancements in extracellular vesicles biomanufacturing: a comprehensive overview of large-scale production and clinical research - Li, Ziqian; Yan, Junyu; Li, Xiang; Chen, Hui; Lin, Chen; Zhang, Yuhang; Gao, Tian; Zhang, Yabo; Shu, Yue; Pan, Shuyuan; Zhang, Yuntao (Frontiers in Bioengineering and Biotechnology, 2025)
Extracellular vesicles (EVs) are nano-sized, membranous structures secreted by cells into the extracellular space, have attracted considerable attention in the field of biosciences for their role in intercellular communication in various physiological and pathological processes. Their ubiquitous presence in bodily fluids and cell-specific characteristics make them promising candidates as biomarkers. Additionally, their ability to transport biological therapeutics across different biological barriers to specific target cells underscores their significant translational potential for diagnostic and therapeutic purposes. Significant progress has been achieved in the translation of EVs research to clinical applications, however, challenges persist in the large-scale production of EVs, particularly in the areas of scalable manufacturing, efficient isolation methods, drug loading techniques, and advanced characterization technology. This review critically examines the complex processes involved in EVs biogenesis and explores recent developments in large-scale EVs production. By synthesizing knowledge from these fields, this review aims to provide a holistic perspective on the evolving landscape of EVs research and its applications, underscoring both the accomplishments and the obstacles that lie ahead in fully realizing the potential of EVs in biomedicine.